The perils of inhibiting deficient factors. (5th July 2018) - Sayar, Z.; Speed, V.; Patel, J. P.; Patel, R. K.; Arya, R.
Abstract : Essentials Anticoagulation in patients with factor X deficiency is an evidence‐poor area. A patient with factor X deficiency was anticoagulated with warfarin followed by rivaroxaban. Warfarin may be a safer anticoagulant option than rivaroxaban in hereditary factor X deficiency. A baseline coagulation screen should be performed prior to commencement of anticoagulation. Summary: We report a case of a previously undiagnosed factor X deficiency in an 83‐year‐old man who had no previous bleeding history despite multiple hemostatic challenges. He was anticoagulated with warfarin for atrial fibrillation without bleeding complications; however, major hemorrhage occurred soon after a switch to rivaroxaban.